2018
DOI: 10.1080/17483107.2018.1493751
|View full text |Cite
|
Sign up to set email alerts
|

Does treadmill training with Hybrid Assistive Limb (HAL) impact the quality of life? A first case series in the United States

Abstract: Our study details the first experience in a larger series regarding the effects of HAL-assisted treadmill training on quality of life. Whereas five out of six patients showed improvements in mobility scores, only one patient showed improvement of life quality at 6 months follow-up. Life quality is influenced by a multitude of factors and lager randomized trials are needed to assess the effect of HAL-assisted training on quality of life. Implications for Rehabilitation Treadmill training with HAL is safe and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…At present, several studies have explored the use of HAL for gait training in different stages after stroke [77][78][79][80][81][82][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. The studies differ in terms of aim, design, duration of intervention, diagnosis, setting, and patient characteristics as well as allocation, randomization, blinding and outcome measures.…”
Section: Hal For Gait Training After Strokementioning
confidence: 99%
See 2 more Smart Citations
“…At present, several studies have explored the use of HAL for gait training in different stages after stroke [77][78][79][80][81][82][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. The studies differ in terms of aim, design, duration of intervention, diagnosis, setting, and patient characteristics as well as allocation, randomization, blinding and outcome measures.…”
Section: Hal For Gait Training After Strokementioning
confidence: 99%
“…no control group is applied) [77-79, 81, 84-88, 90, 91, 94, 95, 99, 101], one is a case study [98], five studies have a control group (but did not use strict randomization) [82,89,92,97,100] and two are randomized controlled trials [80,93,96]. The studies include one [98,99] to 53 [86] patients with stroke who performed HAL training. The total number of HAL sessions range from 1 [87] to 31 [88] and with a total mean of approximately 11 sessions, using HAL 2-3 times per week with durations of ≥20 minutes (net walking time) per session.…”
Section: Hal For Gait Training After Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our recent study found that the degree of improvement throughout VDE-BWSTT for persons with chronic SCI depended on the baseline walking ability [15]. In contrast, to our knowledge, no study and only very few case reports demonstrated the effects of VDE-BWSTT on the QOL of persons with chronic SCI [16,17]. Cruciger et al .…”
Section: Introductionmentioning
confidence: 99%
“…[16] reported that two persons with chronic SCI had improved not only walking ability but also neuropathic pain and health-related QOL with VDE-BWSTT, whereas Yilmaz et al . [17] reported no remarkable effect in one person with SCI. A clinical study with large number of patients is needed to assess the effects of VDW-BWSTT on QOL.…”
Section: Introductionmentioning
confidence: 99%